The role of endplate injury in intervertebral disc degeneration after vertebral augmentation in OVCF patients - Li, Yongchao; Su, Qihang; Feng, Xiaofei; Li, Lijun; Tan, Jun; Ke, Rongjun (Frontiers in Surgery, 2023)
Background: Whether vertebral augmentation can induce or aggravate the degeneration of adjacent intervertebral discs remains controversial. The purpose of this study is to explore the role of endplate injury in intervertebral disc degeneration after vertebral augmentation. Methods: The imaging data of patients with single-segment osteoporotic vertebral compression fractures (OVCFs) were retrospectively analyzed. The upper and lower discs of the fractured vertebrae were defined as cranial and caudal discs, and the discs adjacent to the cranial discs were defined as control discs. According to the integrity of the cranial and caudal endplates, they were divided into an injury group and a noninjury group. At follow-up, the increase in the modified Pfirrmann score on MRI compared with the baseline grade was defined as the occurrence of a degenerative disc change (DDC). The changes in the disc height and the number of DDC cases on MRI during the follow-up in each group were analyzed. Results: A total of 56 patients with OVCFs were included in this study, with an average follow-up time of 18.8 ± 14.1 months. In the cranial and caudal discs, the number of DDC cases in the endplate injury group was significantly higher than that in the noninjury group (P=0.007 and P=0.018). However, the number of DDC cases in the whole endplate injury group (including the cranial and caudal endplates) was significantly higher than that of the noninjury group (P=0.000) and the control group (P=0.000). The number of DDC cases in the whole noninjury group was not different from that of the control group (P=0.192). At follow-up, the disc height of the cranial and caudal endplate injury group was significantly lower than the baseline (P=0.000 and P=0.001), but the disc height of the noninjury group was not significantly lower than the baseline (P=0.074 and P=0.082). Conclusion: Endplate injury is a risk factor for adjacent intervertebral disc degeneration in OVCF patients after vertebral augmentation. Evaluation of endplate damage before vertebral enhancement in OVCF patients has an important reference value for predicting the outcome of adjacent intervertebral discs after surgery.